Arthralgia of the Temporomandibular Joint (Case report) - H. Fikáčková; T. Dostálová; R. Vošická; V. Peterová; L. Navrátil; J. Lesák (Czech Dental Chamber, 2006)
Temporomandibular joint disorders (TMD) is a collective term for dysfunctions associated with the temporomandibular joint and masticatory muscles. In the therapy of TMD the complex conservative treatment facilitates natural regeneration capabilities of the organism is prefered to irreversible therapy based on ideal biomechanics of the temporomandibular joint (TMJ).This report describes the complex treatment of TMJ arthralgia by low level laser therapy (GaAlAs diode laser, energy of density 15 J/cm2), physiotherapy, stabilization splint and prosthetic treatment. Treatment results were objectively confirmed by infrared thermography and magnetic resonance examination.